Dual bronchodilation with tiotropium/olodaterol further reduces activity-related breathlessness versus tiotropium alone in COPD - Maltais, François (Eur Respir J, 2019)
The 3-min constant speed shuttle test (CSST) was used to examine the effect of tiotropium/olodaterol compared with tiotropium at reducing activity-related breathlessness in patients with chronic obstructive pulmonary disease (COPD). This was a randomised, double-blind, two-period crossover study including COPD patients with moderate to severe pulmonary impairment, lung hyperinflation at rest and a Mahler Baseline Dyspnoea Index <8. Patients received 6 weeks of tiotropium/olodaterol 5/5 µg and tiotropium 5 µg in a randomised order with a 3-week washout period. The speed for the 3-min CSST was determined for each patient such that an intensity of breathing discomfort ≥4 (“somewhat severe”) on the modified Borg scale was reached at the end of a completed 3-min CSST. After 6 weeks, there was a decrease in the intensity of breathlessness (Borg dyspnoea score) at the end of the 3-min CSST from baseline with both tiotropium (mean –0.968, 95% CI −1.238– −0.698; n=100) and tiotropium/olodaterol (mean −1.325, 95% CI −1.594– −1.056; n=101). The decrease in breathlessness was statistically significantly greater with tiotropium/olodaterol versus tiotropium (treatment difference −0.357, 95% CI −0.661– −0.053; p=0.0217). Tiotropium/olodaterol reduced activity-related breathlessness more than tiotropium in dyspnoeic patients with moderate to severe COPD exhibiting lung hyperinflation.